ทุนวัฒนธรรมกับวัตถุมงคลในปัจจุบัน - สุจฉายา, สุกัญญา (Journal of Letters, 2016)
นับตั้งแต่รัฐบาลได้วางยุทธศาสตร์กำหนดให้นำทุนทางวัฒนธรรม มาสร้างมูลค่าเพิ่มทางเศรษฐกิจ ดังปรากฏในยุทธศาสตร์ที่ 6 ของแผนแม่บทวัฒนธรรมแห่งชาติ (พ.ศ. 2550-2559) วัตถุมงคลของไทยได้กลายเป็นสินค้าวัฒนธรรมที่ขยายตัวอย่างมากมายทั้งในประเทศและต่างประเทศ บทความนี้มีวัตถุประสงค์ที่จะแสดงให้เห็นว่าวัตถุมงคลเป็นทุนทางวัฒนธรรมอย่างไร วัฒนธรรมที่ฝังตัว (embodied culture) อยู่ในวัตถุมงคลคืออะไร และมีอะไรความแตกต่างของวัฒนธรรมที่ฝังตัวในวัตถุมงคลมีผลอย่างไรต่อความหลากหลายของวัตถุมงคล ผลจากการศึกษาพบว่าวัตถุมงคลเป็นทุนทางวัฒนธรรมที่มีวัฒนธรรมฝังตัวอยู่ 5 ประการ ได้แก่ ความเชื่อในวัตถุมงคลว่าเป็นของศักดิ์สิทธิ์ ความเชื่อในผู้สร้างวัตถุมงคล ความเชื่อและพิธีกรรมในการสร้างวัตถุมงคล เรื่องเล่าหรือนิทานประกอบวัตถุมงคลและพิธีกรรมในการบูชา (การใช้)วัตถุมงคล เพื่อประสิทธิผล วัตถุมงคลที่ผลิตขึ้นในปัจจุบันส่วนใหญ่จึงสร้างขึ้นจากคติชนประเภทนิทานผสมผสานกับความเชื่อ ความหลากหลายของวัฒนธรรมที่ฝังตัวอยู่นี้มีส่วนในการเพิ่มมูลค่าให้กับวัตถุมงคล ขณะเดียวกันก็มีส่วนใน การลดทอนคุณค่าของวัตถุมงคลด้วยเช่นกัน Cultural Capital and Today’s Sacred Objects Sukanya Sujachaya Associate Professor, Department of Thai, and Director, Center of Folklore Research, Faculty of Arts, Chulalongkorn University Since the government has incorporated in the country’s Cultural Master Plan (2007-2016) a sixth strategy stating that cultural capital be used to increase Thailand’s economic value, the trade in sacred objects as cultural products has expanded both domestically and abroad. This article is aimed at explaining how sacred objects are cultural capital, what cultural elements are embodied in the objects, and what effects the varieties of these embodied elements have on the diversity of sacred objects. The study has found that sacred objects as cultural capital contain five embodied cultural elements: the belief that sacred objects are holy, faith in the creator of the objects, beliefs and rituals involved in their creation, legends and stories about the objects, and rituals involved in the use of the objects. The most effective driver in the production of sacred objects today is a combination of folk tales and beliefs. These diverse embodied cultural elements have both increased and decreased the value of sacred objects.